Agama dan Postmodern (Analisis Studi Gender Pendekatan Ilmu Dakwah) - sari, Etika (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2024)
Gender equality is part of social equality in which every citizen regardless of differences in taste, ethnicity, religion, economic class has the same rights. So the researchers took the title (Religion and Postmodernism Gender analysis) as a formula: How to describe and explain Reality and its Implications Gender equality in the postmodern and Islamic era, How to describe and explain Religion in facing postmodern challenges on Gender equality?. This research uses qualitative research with in-depth interviews on random sampling respondents. The results of this study are that reality shows that policies that are issued are not gender responsive and even discriminatory. discriminatory policies. The factors in this matter are the existence of different perspectives regarding gender human rights, the capacity to understand and carry out basic tasks, constitutional and institutional relations. The implication that has been running is that some women have become part of government regulations, many communities and NGOs have become part of the main actors as gender equality. Religion faces postmodern challenges to gender equality, namely religion offers postmodernism in protecting its followers. At this time it becomes a challenge for the superiority of Western intellectuals who have reached the highest point of discovery. Religion is seen as material teachers, but also as Western intellectuals in a spiritual void. Religion and its adherents are still considered spiritual teachers who invite this postmodern era to return to the creator, in order to be balanced in responding to one's mental emptiness and one's nature as a human being regardless of one's gender.